30.2k views
5 votes
Solve: 5x-3+2x = 5x+3 show your work

User Jerrel
by
4.9k points

2 Answers

7 votes

Answer:

x = 3

Explanation:

5x - 3 + 2x = 5x + 3

subtract 5x from both sides

5x - 5x - 3 + 2x = 5x - 5x + 3

-3 + 2x = 3

add 3 to both sides

-3 + 3 + 2x = 3 + 3

2x = 6

divide both sides by 2

2x/2 = 6/2

x = 6/2

x = 3

User Rockyb
by
5.2k points
5 votes

Answer:

x = 3

Explanation:

5x - 3 + 2x = 5x + 3. that is

7x - 3 = 5x + 3 ( subtract 5x from both sides )

2x - 3 = 3 ( add 3 to both sides )

2x = 6 ( divide both sides by 2 )

x = 3

User Kitae
by
4.6k points